(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article presents the results of testing domestic and foreign varieties of table carrots in the desert soil-climatic zone of the Surkhandarya region. An assessment was given to 22 varieties of table carrots in terms of productivity and quality of the crop.